2022
DOI: 10.1111/dth.15757
|View full text |Cite
|
Sign up to set email alerts
|

Ustekinumab to guselkumab transitions: A series of 54 patients emulating the navigate trial in real life

Abstract: NAVIGATE clinical trial demonstrated a higher rate of Psoriasis Assesment Severity Index (PASI)90 response in patients treated with guselkumab when compared to ustekinumab and an improved response in those who switched from ustekinumab to guselkumab due to partial response. The objective of the study is to describe ustekinumab to guselkumab switching in clinical practice. Observational, multicentric, descriptive study including 54 psoriasis patients who switched to guselkumab after treatment with ustekinumab f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
2
7
2
Order By: Relevance
“…Our retrospective study is one of the largest real‐life studies on guselkumab use in patients who failed ustekinumab, with a population of 233 patients. Our study confirmed data from both clinical trials and real‐life studies on the effectiveness of guselkumab in daily clinical practice in patients affected by moderate‐to‐severe plaque psoriasis with previous exposure to ustekinumab 12,14,16,17 . Compared with the Phase 3 clinical trial NAVIGATE, 12 which evaluated the effectiveness of guselkumab in patients with inadequate response to ustekinumab in 135 patients, our cohort was larger at baseline.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Our retrospective study is one of the largest real‐life studies on guselkumab use in patients who failed ustekinumab, with a population of 233 patients. Our study confirmed data from both clinical trials and real‐life studies on the effectiveness of guselkumab in daily clinical practice in patients affected by moderate‐to‐severe plaque psoriasis with previous exposure to ustekinumab 12,14,16,17 . Compared with the Phase 3 clinical trial NAVIGATE, 12 which evaluated the effectiveness of guselkumab in patients with inadequate response to ustekinumab in 135 patients, our cohort was larger at baseline.…”
Section: Discussionsupporting
confidence: 76%
“…Our study confirmed data from both clinical trials and real-life studies on the effectiveness of guselkumab in daily clinical practice in patients affected by moderate-to-severe plaque psoriasis with previous exposure to ustekinumab. 12,14,16,17 Compared with the Phase 3 clinical trial NAVIGATE, 12 which evaluated the effectiveness of guselkumab in patients with inadequate response to ustekinumab in 135 patients, our cohort was larger at baseline. Our population was slightly older (with a mean age of 54.27 years vs. 44.2 years), with a lower BMI (27.56 vs. 30.3) and also included patients with previous exposure to anti-IL-17 drugs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations